การวิเคราะห์บริเวณที่ได้รับผลกระทบจากความร้อนของการเชื่อมแบบใต้ฟลักซ์ สำหรับชิ้นงานเหล็กกล้า - ศุภกาล ตุ้ยเต็มวงศ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study is the analysis of heat affected zone (HAZ) from submerged arc welding for steel work. The objective is to study the welding result from carbon steel by different heat inputs. The submerged arc welding was used in this study by 2 different types of carbon steel ; SS400 and S50C for welding object size 200 x 300 x 10 mm. with 5 different heat inputs ; 6686, 9600, 12857, 16457 and 20400 KJ/cm. The researcher found the increasing of heat input in each level according to the physical characteristics and macrostructure of welding by carbon steel SS400 and S50C as a result of the expansion of heat affected zone (HAZ). The heat level of 16,457 and 20,400 KJ/cm will provide the rendered appropriate welds in terms of physical appearances and macrostructure. For the mechanical result of hardness according to the heat affected zone (HAZ) and tension test for 16,457 KJ/cm, the welding with 300 amps and 32 volts by speed 35 centimeters per minute for carbon steel SS400 and S50C presents the best result for welding object size 200 x 300 x 10 mm. However, since the carbon steel properties of carbon steel SS400 and S50C are different, the result of the study for these 2 carbon steels is different.